Chemokine‐like factor 1 (CKLF1) aggravates neointimal hyperplasia through activating the NF‐κB /VCAM‐1 pathway. Issue 9 (14th August 2020) - Liu, Xinnong; Qu, Chengjia; Zhang, Yongbao; Fang, Jie; Teng, Lequn; Zhang, Rujiao; Zhang, Xiangyu; Shen, Chenyang
Abstract : Neointimal hyperplasia (NIH) is a complicated inflammatory process contributing to vascular restenosis. The present study aimed to explore whether chemokine‐like factor 1 (CKLF1) aggravates NIH via the nuclear factor‐kappa B (NF‐κB)/vascular cell adhesion molecule‐1 (VCAM‐1) pathway. We found the expression of CKLF1 and VCAM‐1 significantly increased in human carotid plaques compared to the control. In vivo, CKLF1 overexpression induced a thicker neointimal formation and VCAM‐1 expression was correspondingly upregulated. In vitro, CKLF1 activated NF‐κB and induced VCAM‐1 upregulation in human aortic smooth muscle cells (HASMCs). Functional experiments demonstrated that CKLF1 promoted monocyte adhesion and HASMC migration via VCAM‐1. These results suggest CKLF1 accelerates NIH by promoting monocyte adhesion and HASMC migration via the NF‐κB/VCAM‐1 pathway. Our findings contribute to a better understanding of the mechanisms underlying the causality of CKLF1 on NIH and could prove beneficial in designing therapeutic modalities with a focus on CKLF1. Abstract : Neointimal hyperplasia (NIH) plays a pivotal role in vascular restenosis after revascularization. We previously identified that chemokine‐like factor 1 (CKLF1) could aggravate NIH by arresting smooth muscle cells in G2/M phase and preventing apoptosis via phosphoinositide 3‐kinase/AKT/nuclear factor‐kappa B signaling. Here, we demonstrate that CKLF1 promotes monocyte adhesion and smooth muscle cell migration via VCAM‐1. Our work furthers our understanding of how CKLF1 contributes to NIH causality.